MAPK-dependent copper tolerance mechanisms revealed by integrated physiology and transcriptomics in peanut - Bao, XueFeng; Ning, WeiMin; Gao, ZhiQiang; Hu, Mian; Dong, Xuan (Frontiers in Plant Science, 2025)
IntroductionTo elucidate the physiological and molecular responses of peanut (Arachis hypogaea L L. c.v. ‘Haihua No. 1’) to copper stress, this study aimed to investigate the changes in root morphology, ion content, oxidative stress, and gene expression under copper stress conditions.MethodsSeedlings were exposed to 0 (control) or 50 mg/L CuSO₄ solution, with three biological replicates for each treatment. Root length and biomass were measured quantitatively, along with tissue contents of eight ions (K+, Na+, Mg2+, Ca2+, Fe3+, Mn2+, Cu2+, Zn2+), secondary oxidative stress indices, and activities of key antioxidant enzymes. RNA-seq and qPCR validation were performed to analyze transcriptional changes and identify specific gene-response modules in peanut seedling roots under copper stress.ResultsCopper stress significantly induced the expression of MPK4, a key component of the MPK4 pathway. Post-translationally, MPK4 likely phosphorylated two critical protein classes: NAC and LBD. NAC functioned as a core transcription factor, directly regulating the transcription of copper defense-related genes. LBD directly down-regulated genes associated with lateral root growth, indirectly promoting the expression of genes involved in GSH-dependent heavy metal detoxification and secondary oxidative stress (e.g., GST and POD), thereby enhancing the plant's detoxification and antioxidant capacity.DiscussionThis study provides insights into the regulatory mechanisms that peanut plants employ to cope with copper stress. The findings highlight the roles of MPK4, NAC, and LBD in the plant's response to copper stress and suggest that these genes could be targeted in breeding programs to develop copper-tolerant peanut cultivars. The results may provide theoretical support for the development of such cultivars.